2001
DOI: 10.1034/j.1600-051x.2001.028005430.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect an association with IL1 genotypes in European Caucasians with generalised early onset periodontitis

Abstract: The lack of any association between the IL1 polymorphisms and GEOP, in the population presented here, brings into doubt the usefulness of these candidate genes as markers of susceptibility to this form of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
66
4
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 41 publications
18
66
4
8
Order By: Relevance
“…Further, but nonsignificant, support for this result comes from both the model fitting, which gives the LDU location at the peak of this marker, and from the haplotype evidence, which determines the IL-1B þ 3953 -IL-1B À511 haplotype as having the lowest P-value in the region (P ¼ 0.103). This result is in agreement with other studies [37][38][39] which identified the IL-1B þ 3953 polymorphism as implicated in AP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Further, but nonsignificant, support for this result comes from both the model fitting, which gives the LDU location at the peak of this marker, and from the haplotype evidence, which determines the IL-1B þ 3953 -IL-1B À511 haplotype as having the lowest P-value in the region (P ¼ 0.103). This result is in agreement with other studies [37][38][39] which identified the IL-1B þ 3953 polymorphism as implicated in AP.…”
Section: Discussionsupporting
confidence: 93%
“…We also note that the case group is of the same magnitude as some other published studies on different ethnic groups. 38,[40][41] In conclusion, the presence of recombination hot spots between the IL-1B þ 3953 and IL-1B À511 polymorphisms and around the IL-1RN (VNTR) marker suggests that dense SNP typing within these regions will be required to fully determine an extended informative haplotype structure and its possible associations with disease. Greater precision and perhaps significance might be achieved by typing more SNPs in the immediate IL-1B þ 3953 region and, of course, through meta-analysis of other data sets with larger-scale well-controlled designs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The association between a composite genotype of allele 2 of IL1B +3953 gene and allele 2 of IL1A -889 gene in severe form of adult periodontitis was published (35). Our results of composite IL1 genotype in Macedonian patients with periodontitis are in agreement with several published papers in which no signifi cant association between composite genotype of IL1 with periodontitis was found (36)(37)(38) A most recent study has shown that genotype 2/2 of IL1RN for the whole Brazilian population and allele T of IL1B (C-511T) in a subgroup of Afro-Americans and mulattos were suggested to be putative risk indicators for chronic periodontitis (39).…”
Section: Discussionsupporting
confidence: 83%
“…Çevresel ve genetik faktörler ise konak bağışıklık yanıtını, bağ dokusu ve kemik metabolizmasını etkileyerek periodontal hastalığın oluşmasına katkıda bulunurlar. 18,19 Hart ve Kenneth, 2 periodontal hastalıkları genetik olarak inceledikleri çalışmada, riskli ve sağ-lıklı bireyler arasındaki farklılıkların immün sistemin elemanlarını kodlayan genlerdeki polimorfizmler olduğunu belirtmişlerdir.…”
Section: Introductionunclassified